Hubungan Pengetahuan tentang Covid-19 dengan Kepatuhan Menjalankan Protokol Kesehatan pada Mahasiswa Fakultas Non-Kesehatan Universitas Harapan Bangsa - Wilujeng Pangesti; Feti Kumala Dewi; Murniati Murniati; Maya Safitri (Poltekkes Kemenkes Bengkulu, 2022)
The number of Covid-19 cases is still increasing. This is due to a lack of discipline in complying with health protocols. Knowledge is something that affects the creation of compliance. The purpose of this study was to determine the correlation between knowledge about Covid-19 and obedience to do health protocols among non-health faculty students at Harapan Bangsa University. This type of research is quantitative with a cross - sectional approach. The sampling method used a total sampling of 122 students of the Non-Health Faculty, Universitas Harapan Bangsa. Data collected by online distributing questionnaires using a google form. The results of the study obtained the value of Sig. 2-tailed is 0.000 (p-value > 0.005), meaning that there is a correlation between knowledge of Covid-19 and obedience to health protocols among non-health faculty students at Universitas Harapan Bangsa. The Correlation Coefficient value is 0.568, which means that the correlation is included in the type of moderate relationship strength. This research is expected to be an illustration for students about the relationship between knowledge and obedience with health protocols so that students are expected to be more concerned about preventing Covid-19.